Inter-species comparative antioxidant assay and HPTLC analysis of sakuranetin in the chloroform and ethanol extracts of aerial parts of Rhus retinorrhoea and Rhus tripartita. (1st January 2017) - Alam, Perwez; Parvez, Mohammad Khalid; Arbab, Ahmed Hassan; Siddiqui, Nasir Ali; Al-Dosary, Mohammed Salem; Al-Rehaily, Adnan Jathlan; Ahmed, Sarfaraz; Kalam, Mohd Abul; Ahmad, Mohammad Shamim
Abstract: Context: Extensive research on Rhus (Anacardiaceae) shows their antioxidant potential, which warrants further evaluation of its other species. Objective: To perform a comparative antioxidant assay on extracts of R. retinorrhoea and R. tripartita, including sakuranetin quantification by a validated HPTLC method. Materials and methods: In vitro antioxidant assay was performed on chloroform and ethanol extracts of R. retinorrhoea Steud. ex Oliv. (RRCE and RREE) and R. tripartita (Ucria) Grande (RTCE and RTEE) by DPPH radical scavenging (at 31.25, 62.5, 125, 250 and 500 μg/mL concentrations) and β-carotene-linoleic acid bleaching methods at 500 μg/mL concentration. Densitometric HPTLC method was developed and validated using toluene: ethyl acetate: methanol (8:2:0.2; v/v/v) as mobile phase, executed on glass-backed silica gel F254 plate and scanned at 292 nm. Results: Antioxidant activity of Rhus extracts tested by the two methods (DPPH/BCB) was found in order of RTEE > RREE > RTCE > RRCE with IC50 118.67/256.26, 315.75/82.35, 827.92/380.0 and 443.69/292.75, respectively. Scanning of the HPTLC plate provided an intense peak of sakuranetin at Rf = 0.59. The estimated sakuranetin content in the dry weight of the extracts was highest in RREE (27.95 μg/mg) followed by RRCE (25.22 μg/mg), RTEE (0.487 μg/mg) and RTCE (0.0 μg/mg). Presence of sakuranetin in RREE, RRCE and RTEE supported the highest antioxidant property of the two Rhus species. Nonetheless, low sakuratenin in R. tripartita indicated the presence of other bioactive constituents responsible for synergistic antioxidant activity. Conclusion: The developed HPTLC method therefore guarantees its application in quality control of commercialized herbal drugs and formulations containing sakuranetin.